Organizational Responses to Institutional Pressures: Reconfiguration of Spaces in Nanosciences and Nanotechnologies. Issue 11 (November 2017) - Battard, Nicolas; Donnelly, Paul F.; Mangematin, Vincent
The literature on organizational responses to institutional pressures describes responses ranging from compliance to resistance via different modes of decoupling. However, although these studies provide a greater understanding of the phenomenon, they tend to consider the different elements separately. Through a comparative case study of six research teams in the area of nanosciences and nanotechnologies, we offer three contributions. Our first contribution is to the decoupling literature by way of a complementary and cohesive framework, which shows that organizations vary in their responses by reconfiguring their physical (policy and materiality), mental (meaning) and social (identity) spaces, and that each space can be reconfigured at the core or periphery, or not be reconfigured. Our second and third contributions are through descriptions of two modes of organizational responses to institutional pressures and two factors explaining the variety of responses.